Comparative evaluation of the effectiveness of natural silicon mineral waters and their artificial analogics on the current experimental patiology of sleeve-surface tract - Gushcha, S. G.; Nasibullin, B. A.; Nikipelova, E. M.; Badiuk, N. S. (Journal of Education, Health and Sport, 2019)
The article presents data on the effect of silicon-containing mineral waters (MW) and their artificial analogues with the corresponding content of metasilicic acid on the state of the stomach wall in the modeling of gastritis in white rats. It was established that the use of MW with different content of metasilicic acid has a unidirectional, positive effect on the course of gastritis. MW with greater mineralization, molarity and high content of methacrylic acid completely eliminate inflammation and moderately stimulate reparative processes. In the application of MW with less mineralization, molarity and lower content of metasilicic acid, there were definitive inflammation manifestations, but the manifestations of reparative processes were more pronounced. The same trend was observed with the use of artificial analogues - model solutions on distilled water with the corresponding content of metasilicic acid. It is determined the same restorative in the direction, but much weaker corrective effect than the corresponding MW. The important component of the corrective action of these silicon MW when used in animals with gastritis is determined by the peculiarities of the macro component composition and the proportion of the main macro components - Na +, K +, Mg2 +, Ca2 +, НСО3, Cl-, SO42- and, to a lesser extent, silicon content.